Persistence of viral RNA in the brain of experimentally infected mice with coxsackievirus B5 - Stipalova, D.; Sojka, M.; Borsanyiova, M.; Badurova, M.; Marosova, L.; Sobotova, Z.; Bopegamage, S. (Вiopolymers and Cell, 2011)
Aim. The aim of our study was to follow the persistence of viral RNA in selected organs of experimentally infected with coxsackievirus (CV) B5 strains from different sources such as a patient’s sample, an environmental sample and a prototype virus strain. Methods. CD-1 mice were infected with CVB5 strain Faulkner the prototype, CVB5 – isolate from treated sewage waste and isolate from patient’s stool sample both identified as CVB5. The viral RNA was detected by RT-PCR using enterovirus primers specific for the non-coding 5' region. Results. We observed presence of RNA in the brain and heart of mice infected with isolate from patient’s stool at day 45 post infection (p. i.). Conclusion. We conclude that CVB5 persists in the brain and heart after oral infection of CD1 mice. The relevance of viral persistence maybe related viral origin and the genetics. Keywords: coxsackievirus B5, mouse, brain, persistence.